2016
DOI: 10.1101/gad.287235.116
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ promotes metabolic adaptation to glutamine deprivation via phosphorylation and inhibition of PFKFB3

Abstract: Glutamine is an essential nutrient for cancer cell survival and proliferation. Enhanced utilization of glutamine often depletes its local supply, yet how cancer cells adapt to low glutamine conditions is largely unknown. Here, we report that IκB kinase β (IKKβ) is activated upon glutamine deprivation and is required for cell survival independently of NF-κB transcription. We demonstrate that IKKβ directly interacts with and phosphorylates 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase isoform 3 (PFKFB3), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 64 publications
(73 reference statements)
0
50
0
Order By: Relevance
“…These results suggest that GLUL's function is limited under glutamine deprivation in those lung cancer cells. In fact, cancer cells can utilize many other ways to sustain cell proliferation and survival when deprived of glutamine (Cheng et al, 2011;Reid et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that GLUL's function is limited under glutamine deprivation in those lung cancer cells. In fact, cancer cells can utilize many other ways to sustain cell proliferation and survival when deprived of glutamine (Cheng et al, 2011;Reid et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As examples, one study found that the requirements for glutamine undergo changes upon transition from monolayer culture to anchorage-independent culture [7], and another study found that glutamine catabolism was not required for tumorigenesis in vivo in some mouse models, which led to the conclusion that glutamine metabolism may not have a role in cancer [13]. Nevertheless, numerous other studies have provided compelling evidence that a requirement for glutamine catabolism indeed exists in many in vivo settings [10, 1421]. In this review, we discuss these seemingly contradictory recent findings in detail and explain the factors underlying the heterogeneity of glutamine metabolism in cancer.…”
Section: Metabolic Reprogramming In Cancermentioning
confidence: 99%
“…Glutamine is required for cell survival (16)(17)(18)(19), and its loss induced cell death ( Fig. 1A; Supplementary Fig.…”
Section: Requirement Of Glutamine-nitrogen For Cell Survivalmentioning
confidence: 99%